1997
DOI: 10.1152/ajplung.1997.272.2.l253
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 receptor blockade prevents airway responses induced by antigen challenge in mice

Abstract: The functional role of interleukin (IL)-4 in the development of airway hyperresponsiveness (AHR) and pulmonary eosinophilia in response to sensitization and challenge of mice with sheep red blood cells (SRBC) was examined. Control- and SRBC-sensitized A/J mice were treated with an antibody to the murine IL-4 receptor (anti-IL-4R) 3 days before intratracheal challenge with the antigen or vehicle only. Blockade of IL-4R significantly reduced antigen-induced AHR and prevented increases in goblet cells and broncho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
97
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 0 publications
10
97
0
2
Order By: Relevance
“…Because therapeutic targeting of IL-4R␣ substantially decreases eosinophilia in response to allergen challenge (27), an IL-13R␣1-independent pathway for eosinophil recruitment that is efficiently induced by IL-4 through the type I IL-4R must exist. Our in vitro chemotaxis studies support the existence of a CC chemokineindependent pathway for eosinophil recruitment under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Because therapeutic targeting of IL-4R␣ substantially decreases eosinophilia in response to allergen challenge (27), an IL-13R␣1-independent pathway for eosinophil recruitment that is efficiently induced by IL-4 through the type I IL-4R must exist. Our in vitro chemotaxis studies support the existence of a CC chemokineindependent pathway for eosinophil recruitment under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the therapeutic effect of CpG on eosinophilic inflammation, IgE levels, and AHR in this model may be a result of down-regulation of TH2 cytokine levels. Previous studies showed that anti-IL-4 or anti-IL-13 receptor Abs suppressed Ag-induced AHR, but not eosinophilic inflammation (32,33), and that anti-IL-5 Ab administered after Ag challenge suppressed eosinophilic inflammation but had little effect on AHR (34). Because natural allergic inflammatory reactions are mediated by a combination of Th2 cytokines, CpG-ODN administration may offer some advantage over therapeutic administration of single Abs against IL-4, IL5, or IL-13, or their receptors.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated the inability of intratracheal OVA-challenge to elicit eosinophil infiltration, mucus hypersecretion and airway hyper-reactivity in mice deficient in either CD4 þ T-cells, IL-4 receptor or STAT6. [4][5][6][7] The T H 2 cytokine IL-13 plays a central role in this model as administration of a soluble IL-13 antagonist (sIL-13Ra2-Fc) completely blocked OVAchallenge induced goblet cell mucus metaplasia and AHR, while intratracheal instillation of mIL-13 fully replicated asthma-related pathologies. 8,9 These results are consistent with the fact that STAT6 activation is downstream of IL-4Ra-mediated signaling and that IL-13 is required for OVA induced AHR and mucus production.…”
Section: Introductionmentioning
confidence: 96%